(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
The design and use of learner corpora is a rapidly developing branch of corpus linguistics. Learner corpora have the signal merit of allowing for the use of evidence-based methods in applied linguistics. This article introduces the Saudi Learners of English Corpus (SLEC), composed of writing by undergraduate students in Saudi universities. The SLEC is presented as the first Saudi written English as a Foreign Language (EFL) corpus that will be made eventually publicly available. It comprises 175,592 words, collected from EFL learners in Saudi Arabia, all of whom have studied English for nine years in Saudi public schools. The corpus includes data produced by 741 students. Their proficiency level ranges between beginner and intermediate. The corpus is designed to include a variety of metadata which describes features of the texts and the learners. The article presents the contents and the design criteria of SLEC, discussing in detail the rationale for the corpus, the participants involved, the corpus size, the materials included, the method of data collection, corpus metadata and architecture. Pedagogical implications and potential future research are also addressed.